Sense-scape: Spatial Perceptions of The Intangible - Le Phan, Thuy Tien (Auckland University of Technology, 2024)
The New Zealand Dream—once symbolized by spacious homes with pools, lawns, and villas—has shifted due to economic pressures, urbanization, and increasing housing density. As homeownership becomes more commodified, smaller, efficient homes like terraced houses and townhouses are growing in popularity. (Stock, 2024). Hailed as the future of suburbia with numerous successful adoptions from other countries (Polacek and Elliott, 2020) (Bushnell, 2024), these medium-density options appeal to younger generations, facing criticism for reducing space and sensory richness. The focus on function and minimization of scale often leads to a loss of sensory and aesthetic values, as seen in cookie-cutter homes that lack individuality and soul. (Almeida, 2023) (Orsman, 2023). Relph (2001) makes a remark on sensory to sense-of-place in the extract “Place in Geography”, referring to the latter as the “attachment to spatial locations” developed from “sensory impressions, memory and imagination.” This research asks whether smaller spaces can retain the sensory qualities of larger ones. It explores how thoughtful design can enhance comfort and intimacy in constrained spaces, challenging the bureaucratic standards that dominate the built environment. Inspired by Pallasmaa’s (2012) The Eyes of the Skin and using a practice-based approach, the thesis investigates multisensory design through autoethnographic reflection, prototyping, and analysis. Following a practice-based research approach, this thesis translates spatial memory into artefacts of sensory experience through a process of autoethnographic reflection, prototyping, and analysis leading to the production of artefacts in combination with various forms of analogue media, informing the scale-production of a 1:1 installations within a constrained space. The outcomes of the thesis have been informed by research on precedents and architectural theories, the study of phenomenology, sketching/mapping as well as relevant case studies on the sense of comfort, scalability and economic-centric design. The implications of the finding of this research. The findings suggest that, with careful design, smaller spaces can provide rich sensory experiences, arguing that urban density can increase without compromising well-being. In essence, size doesn’t matter as long as the space promotes a positive, lived experience.